Strategi Pemasaran di Lembaga Kemanusiaan Dompet Ummat dalam Meningkatkan Kepercayaan Muzakki Kota Pontianak - Rahim, Abdul; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to explore and analyze the marketing strategies implemented by the humanitarian organization Dompet Ummat in building and enhancing the trust of muzakki (zakat donors) in Pontianak City. The research employed a descriptive qualitative method with data collected through observation, in-depth interviews with six key informants, and documentation. The results of the study indicate that Dompet Ummat applies a marketing mix strategy using both offline and online promotional approaches. Offline promotion includes the distribution of brochures, banners, posters, and proposal submissions. Meanwhile, the online promotion is carried out through the utilization of social media platforms such as WhatsApp, Instagram, TikTok, and Facebook. The organization also prioritizes transparency, accountability, and professional service as core approaches in building donor trust. The effectiveness of these marketing strategies is reflected in the increased participation of muzakki, positive testimonials, and repeated zakat contributions. The study concludes that muzakki trust can be significantly enhanced through consistent marketing strategies, open communication, and a human-centered approach.